THE EFFECT OF EXERCISE TRAINING AT HOME ON LIFE QUALITY OF OSTEOARTHRITIS ELDERLY PATIENTS - Orizani, Chindy Maria; Lin, Chueh-Ho (SYNTIFIC, 2025)
Background. Osteoarthritis (OA) is a degenerative joint disease characterized by chronic pain, stiffness, and decreased joint function, which significantly impairs the quality of life in older adults. As OA progresses, it limits mobility and daily functioning, leading to psychological distress and reduced independence. This study aimed to evaluate the effectiveness of Home-Based Exercise Training (HBET) in improving the quality of life among elderly patients with osteoarthritis. Research Methods. A quasi-experimental study with a one-group pretest and posttest design was conducted at the Surabaya Square Public Health Center. Sum of 26 elderly patients diagnosed with knee osteoarthritis were selected through consecutive sampling, meeting specific inclusion criteria. Participants performed HBET knee exercises at home for 2 weeks under guidance. The Osteoarthritis of Knee and Hip Quality of Life (OAKHQOL) questionnaire was used to assess the quality of life before and after the intervention. Data were analyzed using the paired t-test with a significance level set at p <0.05. Findings. Statistical analysis revealed a significant improvement in life quality after the intervention, p-value 0.0001. Participants experienced notable enhancements in physical functioning, pain reduction, emotional well-being, and social engagement after performing regular HBET knee exercises. Conclusions. Home-Based Exercise Training (HBET) effectively enhances life quality for older patients knee osteoarthritis. It is a practical, low-cost, and sustainable intervention that can be implemented in community health programs. Further research is recommended to explore HBET's benefits in other aging-related conditions.